A data-driven approach to customer relationships : a case study of Nedbank's data practices in South Africa - Winig, Laura (Data & Analytics case study series., 2016)
South Afirca's Nedbank is a leader in its market - but to stay in that position, it needed to identify new ways to serve its existing business clientele as well as attract new customers. Its solution: Use the extensive transaction data the bank collects to help customer improve their service.